Pregunta
Solve for \( z \) \[ \begin{array}{l}3(z-14.9)+-7=0.71 \\ z=\square \\ \text { Submit }\end{array} \]
Ask by Coles Burton. in the United States
Feb 03,2025
Solución de tutoría real
Respuesta verificada por el tutor
Responder
\( z = 17.47 \)
Solución
To solve for \( z \) in the equation:
\[
3(z - 14.9) + (-7) = 0.71
\]
**Step 1:** Simplify the equation.
\[
3(z - 14.9) - 7 = 0.71
\]
**Step 2:** Distribute the 3 into the parentheses.
\[
3z - 44.7 - 7 = 0.71
\]
**Step 3:** Combine like terms.
\[
3z - 51.7 = 0.71
\]
**Step 4:** Add 51.7 to both sides to isolate the term with \( z \).
\[
3z = 0.71 + 51.7
\]
\[
3z = 52.41
\]
**Step 5:** Divide both sides by 3 to solve for \( z \).
\[
z = \frac{52.41}{3}
\]
\[
z = 17.47
\]
**Final Answer:**
\[
z = 17.47
\]
Revisado y aprobado por el equipo de tutoría de UpStudy
Como
error msg
Explicar
Simplifique esta solución
Mind Expander
Let's solve for \( z \) step by step. Starting with the equation: \[ 3(z - 14.9) - 7 = 0.71 \] First, we will simplify the equation. Distributing the 3 gives us: \[ 3z - 44.7 - 7 = 0.71 \] Combining like terms leads to: \[ 3z - 51.7 = 0.71 \] Next, we isolate \( 3z \) by adding 51.7 to both sides: \[ 3z = 0.71 + 51.7 \] Calculating the right side: \[ 3z = 52.41 \] Now, divide both sides by 3 to solve for \( z \): \[ z = \frac{52.41}{3} \] Calculating this gives: \[ z = 17.47 \] So, the solution is: \[ z = 17.47 \]
¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde
Hazte Premium